Triatominium search and diagnosis of trypanosoma cruzi in vectors captured in cane calk originating from sugarcane industry (Research, Society and Development, 2021)
The objective of the study was to survey triatomines and diagnose Trypanosoma cruzi in captured vectors and sugarcane juice from sugarcane mills. 100% (3/3) of the active sugar cane mills in the study area were surveyed. An active and passive search of the vectors and research of T. cruzi in the feces of engorged triatomines by compression of the abdomen and for the juice in natura by sedimentation with Giemsa staining technique were carried out, where five samples per mill were collected, totaling 15 researched. As a result, in 100% (3/3) of the mills, 22 hematophagous triatomines were captured, with 41% (9/22) by passive search and 59% (13/22) by active search. 81.8% (18/22) were found in the household environment and 18.2% (04/22) in the intra-household environment of the mills. Two species were identified being 68.18% (15/22) Triatoma brasiliensis and 9.09% (02/22) Triatoma pseudomaculata, with one adult and the four nymphs unable to be identified. T. cruzi diagnosis for triatomines was observed 4.54% (1/22) positive and 95.45% (21/22) negative, while broth, 100% (15/15) negative. However in 33.3% (5/15) broth samples the presence of soiling (microplastics) was observed. Demonstrating the importance of investigation and monitoring of milling sites with the possibility of oral transmission, which currently represent the majority of infection records in Brazil.